Enhanced microporous structure of gamma irradiated agarose-gelatin-HAp flexible films for IR window and microelectronic applications. (September 2020) - Ramya, J. Ramana; Arul, K. Thanigai; Asokan, K.; Ilangovan, R.
Abstract: Flexible free-standing agarose-gelatin-HAp films were prepared by freeze drying route and subsequently followed by gamma irradiation (25 KGy, 50 KGy and 100 KGy). The polymer phase at low dose is enhanced and further it displays reduced inorganic planes. At the AGH-25 (low dose), the NH vibration of the gelatin and the phosphate groups of HAp were suppressed. The pore size of the AGH-100 (high dose) was enhanced (54%) compared to the AGH-25. The reflectance and dielectric constant were tuned on irradiation. Further, disorder, delocalization of charge carrier and pore size are facilitated to reduce dielectric constant of the irradiated films. Thus, it could be a potential candidate for flexible electronics.